Treatment of children and adolescents with hemangioma using propranolol: preliminary results from a retrospective study - Albuquerque, Juliana Costa; Magalhães, Rosane Aline; Félix, Jamille Araújo; Bastos, Maria Vilani Rodrigues; Fontenele, Juvenia Bezerra; Trompieri, Nádia Mendonça; Felix, Francisco Helder Cavalcante (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Hemangiomas are the commonest vascular tumors during childhood. In 2008, the effect of propranolol for treating capillary hemangiomas was demonstrated. Other similar results followed,showing that it rapidly reduces lesion volume. The objective here was to evaluate children and adolescents with hemangiomas that were treated with propranolol. DESIGN AND SETTING: Retrospective study, conducted in a children’s hospital. METHODS: Patients aged 0-19 years with or without previous treatment, who were treated between January 2009 and December 2010, were included. The response was assessed by comparing the lesion appearance between the start of treatment and the last consultation. We considered partial or complete responses as the response to treatment. RESULTS: Sixty-nine patients with a median follow-up of 11 months (mean age: 31 months) were included. Of these, 58 patients were recently diagnosed and 11 had had previous treatment. A response (partial or complete) was seen in 60 patients (87%). Among the capillary hemangioma cases, responses were seen in 50 out of 53 (94%), while in other lesion types, it was 10 out of 16 (63%) (P = 0.3; chi-square). Responses in patients less than one year of age were seen in 37 out of 38 (97%), whereas in those over one year of age, in 23 out of 31 (74%) (P = 0.4; chi-square). Side effects were uncommon and mild. CONCLUSIONS: Propranolol seemed to be effective for treatment of hemangiomas in children and adolescents, and not just in the proliferative stage, with responses in almost all the patient.